Modeling and characterization of hysteresis loops with Preisach hysteron weight modification - Monnor T. (2017)
© 2016 Taylor & Francis Group, LLC. Preisach-based method was used to characterize a series of BaTiO 3 hysteresis loops with varying external field frequencies. A stochastic adjustment of hysterons' weight was performed to obtain the Preisach densities. These densities, in representing the hysteresis responses, were characterized with three key parameters of the 3-dimensional hyperbolic-like distribution. One of the parameters relates directly to coercivity, while the other two concurrently represent polarization derivatives close to the coercivity, and emphasize an adaptability of the material to the external field around the main body of the loops. Thus, this approach can be extended to characterize other series of hysteresis loops to study changes of material responses influenced by varying external field frequency factor.